Klassische Theorien Sozialer Arbeit und soziale Bewegungen Eine wissenssoziologische Verhältnisbestimmung anhand der Begriffsverwendung von "Volk" und "Nation" - Werner, Melanie (Verlag Barbara Budrich, 2023)
Social work has repeatedly placed itself in relation to social movements - but has not defined this relationship further. This book empirically explores the relationship of social work to social movements and looks at the period of social work's emergence - the German Empire and the Weimar Republic. The author asks how the concepts of "people" and "nation" are thematized in journals of the labor movements, the youth movement, and the bourgeois women's movement, as well as in classical theoretical approaches to social work, and what conclusions can be drawn from this about the relationship of social work to social movements.